The effects of an education and exercise-based injury prevention programme on knowledge, eccentric shoulder strength, shoulder range of motion, and thoracic range of motion among competitive youth volleyball athletes: a randomized controlled trial - Lau, R.; Mukherjee, S. (Research in Sports Medicine, 2025)
A 12-week randomized controlled trial was conducted to evaluate the effects of an education and exercise-based programme among competitive youth volleyball athletes. Forty-five participants were randomized into intervention (n = 23) and control groups (n = 22). The intervention group attended the "Education program for youth athletes" in Week 1 and the "Exercise program" over 12 weeks. The education programme improved participants` knowledge scores concerning overuse injuries and the growth and maturation process during adolescence from baseline to Week 12 (p = .001). The exercise programme improved shoulder internal rotation range of motion after 12 weeks (p < .001). No significant improvements were observed for eccentric shoulder external rotation strength and thoracic rotation range of motion following the exercise programme in the intervention group. The education and exercise-based programme improved knowledge regarding overuse injuries and the adolescence growth process and shoulder internal rotation range of motion among youth volleyball athletes.